Developmental and Adult Basic Education Motivation and Optimism/Helplessness Model - Valerie K. Ambrose (Adult Education Research Conference, 2014)
Students in Developmental and Adult Basic Education often have very specific motivational needs; however, there is no model of motivation that describes these students’ experiences. This model synthesizes motivation research on those populations as well as motivational theories and models from psychology (including K-12 educational psychology).